The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1515/agp-2015-0016
|View full text |Cite
|
Sign up to set email alerts
|

Compaction of lignite: a review of methods and results

Abstract: ABSTRACT:Widera, M. 2015. Compation of lignite: a review of methods and results. Acta Geologica Polonica, 65 (3), 367-378. Warszawa.The published peat:coal compaction ratios range from 1.1:1 to 60:1 and from 1.1:1 to 11:1 for lignites. These probably represent realistic end-member values for the degree of compaction during the transformation of peat into lignite and then to coal. Hence, in many cases, the obtained values of the compaction ratio are under-or overestimated with reference to the entire coal seam.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…All of the compaction ratio values discussed herein were obtained by using stratigraphic methods. Furthermore, it is worth noting that only stratigraphic methods allow a direct quantification of the compaction ratio for the entire lignite seam (Widera 2015). The average peat-to-lignite compaction ratio for lignites from the Krzywiń and Złoczew grabens is equal to 2.2 (Kasiński 1984a(Kasiński , 1984b.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All of the compaction ratio values discussed herein were obtained by using stratigraphic methods. Furthermore, it is worth noting that only stratigraphic methods allow a direct quantification of the compaction ratio for the entire lignite seam (Widera 2015). The average peat-to-lignite compaction ratio for lignites from the Krzywiń and Złoczew grabens is equal to 2.2 (Kasiński 1984a(Kasiński , 1984b.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, such an approach results in the reconstructed original peat thickness often being over or underestimated. This is best demonstrated by the very wide range of compaction ratio included in the geological literature, which is between 1.1 and 11.0 for lignite from around the world, as the author of this work previously compiled (Widera 2015).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, a detailed analysis of sediment bodies in the Most Basin showed that the extensive lacustrine clastic strata above the coal seam caused the compaction of the underlying peat to one-seventh of its former thickness, compaction of the fluvial clays to one-third of their former thickness, and negligible compaction of the fluvial sands (Hurník 1972, Mach 2003, Novotný & Mach 2016. Studies of fluvial and deltaic sediment bodies embedded in the local coal seam demonstrated that the compaction of the peat strata contributed to the formation of accommodation space for the fluvial clastics (Dvořák & Mach 1999, Rajchl & Uličný 2005, Rajchl et al 2008, Overviews of this peat compaction and examples from other basins are given by Van Asselen et al (2009), Van Asselen (2011), and Widera (20152016a, b).…”
Section: Geological Settingmentioning
confidence: 99%
“…The lignite studied in the Falklands has been derived from peatland with possibly periodic flooding by brackish waters or seawater. Taking into account that the majority of the peat: lignite compaction ratios for various lignite range from 2:1 to 4:1 as reported by Widera (2015), it can be assumed that the peat thickness prior to burial was 2-4 times greater than today. The observed vascular tissues with sieve plates and fibers are considered here to represent primary vascular tissue, most possibly of herbaceous angiosperms.…”
Section: The Periglacial Subbituminous Coal-sand Unit From the Southementioning
confidence: 99%